Los contactos lingüísticos en Hispanoamérica y en los EEUU: desde el bilingüismo hasta el translingüismo - Petkova, Ingrid (Neophilologica, 2017)
In this article I talk about two types of language contacts: the Hispanic-Indigenous bilingualism in Spanish America and Spanglish in the USA, including different attitudes towards them. Then I introduce the theory of translanguaging, which considers the problems of bilingualism in a quite innovative way that can contribute to the increase in the prestige of bilingualism and code switching.